Placing Ecosystem Services within the Water–Food–Energy–Climate Nexus: A Case Study in Mediterranean Mixed Orchards - Sotiroula Ioannidou; Vassilis Litskas; Menelaos Stavrinides; Ioannis Ν. Vogiatzakis (Agronomy, 2022)
We used Cyprus as a model to link the Water–Energy–Food–Climate (WEFC) nexus indicators (e.g., carbon and water footprints) to the ecosystem services (ES) provided by 39 mixed orchards (stone fruits and nuts) on organic (Org) and conventional (Conv) farms. Food provision was lower for Org than Conv orchards. Management practices in Org mixed orchards better support climate change mitigation and water flow regulation. Soil quality parameters (e.g., organic matter and soil respiration), Arbuscular Mycorrhizal Fungi (AMF), and farm attributes (e.g., tree age) were significantly correlated to the GHG emissions per Mcal of food. Using cluster analysis, orchards were grouped based on WEFC indicators. Finally, a simple approach was developed to allow a rapid link between the WEFC and ES and to support decision making related to land use. This approach highlighted that in the case of Mediterranean mixed orchards, the main objective towards sustainability should be the balance between input management, food production, and ES from agroecosystems, rather than solely the attainment of high yields.